Jenis Rotan, Produk Rotan Olahan Dan Analisis Ekonomi Pada Industri Pengolahan Rotan Komersial di Kota Medan Type Rattan, Rattan Products Processed and Economic Analysis On Commercial Rattan Manufacturing in Medan - Obbi Pardamean Pane; Irawati Azhar; Tito Sucipto (Program studi Kehutanan USU, 2013)
Rattan processing as non-timber forest production creates a range of activities for a variety of rattan industry. This reasearch aim to describe the existence and development of rattan processing industry in the city of Medan, the type and price of raw materials processed rattan and rattan products are traded, and analyze the feasibility of rattan processing industry in the city of Medan. Data obtained through the census rattan processing industry in 21 districts in the city of Medan and guided interviews with selected rattan processing industry and analyze the feasibility in CV Haramas and UD Citra Rotan. The results of reasearch showed that the rattan processing industry is only found in five districts namely 15 industries in Medan Petisah, 3 industries in Medan Helvetia, 3 industries in Medan Sunggal, 2 industries in Johor and 1 industry in Medan Tuntungan. The type and price of the type genera of Calamus rattan and Daemonorops have Rp.2.000-Rp 20,000 per stem or per kg. Processed rattan products are tables, chairs, baskets, hoods serving, place parcel rattan, wicker mirror and semi-finished table with selling prices between 8,000-Rp.400.000 per unit. Based on the R/C ratio and the BEP of both products in the CV. Haramas viable and economically beneficial to the R/C ratio >1 and the lowest BEP 219 of the 300 units (chair products) in CV. Haramas and UD. Citra Rotan the lowest BEP 90 of 100 units from ratttan basket. Keywords: rattan, processed rattan products, rattan industry, economic analysis